Memorial, Reverend Thomas Carr - Ghosh, Ayan (2023)
Memorial to Reverend Thomas Carr, First Bishop of Bombay, erected upon his death (at Somerset, 1859) by his wife, Catherine Emily Carr. In 1817, Thomas Carr joined the service of the East India Company as Chaplain, and in 1833, he was appointed to the Archdeacon of Bombay. He was consecrated Bishop of Bombay on 19th November 1837.